Fetal growth and premature delivery in pregnant women on antiepileptic drugs - Hernández‐Díaz, Sonia; McElrath, Thomas F.; Pennell, Page B.; Hauser, W. Allen; Yerby, Mark; Holmes, Lewis B. (Annals of neurology, 2017)
Objective To evaluate the effects of epilepsy and antiepileptic drugs (AEDs) used during pregnancy on fetal growth and preterm delivery. Methods This study included singleton liveborn infants born to women enrolled in the North American Antiepileptic Drug Pregnancy Registry between 1997 and 2016. Data were collected prospectively through telephone interviews. The prevalence of preterm birth (<37 weeks) and small for gestational age status (SGA) among infants exposed prenatally to AEDs when used by women with epilepsy (WWE) or women without epilepsy (WWOE) was compared with that among infants unexposed to AEDs and born to WWOE. Multivariate log‐binomial regression models were used to estimate relative risks (RRs) and 95% confidence intervals (CIs). Results The study population included infants born to 6,777 AED‐WWE, 696 AED‐WWOE, and 486 no‐AED‐WWOE. The risk of prematurity was 6.2% for no‐AED‐WWOE, 9.3% for AED‐WWE (RR = 1.5, 95% CI = 1.0–2.1), and 10.5% for AED‐WWOE (RR = 1.5, 95% CI = 1.0–2.4). Prenatal exposure to AEDs in WWE and WWOE was associated with a mean lower birth weight of 110 and 136g, respectively, as compared to no‐AED‐WWOE. The prevalence of SGA was 5.0% for no‐AED‐WWOE, 10.9% for AED‐WWE (RR = 2.0, 95% CI = 1.3–3.0), and 11.0% for AED‐WWOE (RR = 1.9, 95% CI = 1.2–2.9). Within users of AEDs in monotherapy, the prevalence of SGA ranged from 7.3% for lamotrigine to 18.5% for topiramate. Interpretation Women on AEDs during pregnancy, whether for epilepsy or for other neuropsychiatric indications, are at a higher risk of delivering prematurely and giving birth to SGA newborns. The risk may vary by drug. Ann Neurol 2017;82:457–465